Peer Attachment and its Implications for Adolescent Development: A Review of Recent Literature - Putri, Shania Andrisa; Yendi, Frischa Meivilona (International Journal of Applied Counseling and Social Sciences, 2024)
This research highlights the significant role of peer attachment in adolescents' social, emotional, and cognitive development. Positive peer attachments can improve mental health and academic achievement while reducing the risk of problematic behavior. On the other hand, relationships with friends who behave negatively can worsen adolescents' emotional state. This study reviewed various literature sources related to peer attachment using a qualitative approach with desk-based and descriptive methods. The results emphasize the importance of school interventions in shaping social skills and healthy relationships. The involvement of parents and teachers also plays a role in creating a supportive friendship environment. In addition, the study recommends a holistic approach that considers cultural, technological, and family factors to help adolescents adapt to the changing social environment.